Contrasting gene expression patterns during floral induction in two Chenopodium ficifolium genotypes reveal putative flowering regulators - Gutiérrez-Larruscain, David; Krüger, Manuela; Abeyawardana, Oushadee A J; Belz, Claudia; Dobrev, Petre I; Vaňková, Radomíra; Eliášová, Kateřina; Vondráková, Zuzana; Juříček, Miloslav; Štorchová, Helena (Plant signaling & behavior, 2025)
Chenopodium ficifolium is a close diploid relative of the tetraploid crop Chenopodium quinoa. Owing to its reproducible germination and seedling development, it becomes a promising model for studying floral induction, providing a basis for the comparison with C. quinoa. Two C. ficifolium genotypes differ in photoperiodic requirement: C. ficifolium 283 accelerates flowering under long days, whereas C. ficifolium 459 flowers earlier under short days. This study conducted a comprehensive transcriptomic and hormonomic analysis of floral induction in the long-day C. ficifolium 283 and compared the findings to previous experiments with the short-day C. ficifolium. Phytohormone concentrations and gene expression profiles during floral induction were largely similar between the two genotypes. However, a subset of genes exhibited contrasting expression patterns, aligning with the genotypes' differing photoperiodic requirements. These genes, predominantly homologs of flowering-related genes in Arabidopsis thaliana, were activated under long days in C. ficifolium 283 and under short days in C. ficifolium 459. Notably, the contrasting expression of the FLOWERING LOCUS T-LIKE 2-1 gene, which was previously shown to induce precocious flowering in A. thaliana, confirmed its role as a floral activator, despite its low expression levels.
Keywords: phytohormones; Genes, Plant; fotoperioda; Genotype; transcriptome; Photoperiod; regulátory růstu rostlin; Flowering; květy; rostlinné proteiny; regulace genové exprese u rostlin; long-day Chenopodium ficifolium; Flowers; Plant Growth Regulators; Gene Expression Regulation, Plant; genes with contrasting expression trends; Chenopodium; genotyp; rostlinné geny; Plant Proteins